ANALISIS SISTEM PENGENDALIAN INTERN ATAS ASET TETAP PADA KANTOR IMIGRASI KELAS 1 PONTIANAK - B41108077, Sri Indriani (Jurnal KIAFE, 2013)
The study was conducted with the aim to find out how the system of internal control over fixed assets at Kantor Imigrasi Kelas 1 Pontianak, to determine the factors that must be considered and implemented so that the system of internal control over fixed assets at Kantor Imigrasi Kelas 1 Pontianak become more effective, and to investigate how the fixed asset accounting policies applied in terms of institutions of Government Accounting Standards No. 07 The method used is descriptive method and form of research is a case study (case study) by taking the object of research at Kantor Imigrasi Kelas 1 Pontianak. Data collection techniques are interviews, observation, documentary studies, library research, questionnaires, with data analysis techniques that evaluate organizational structure, flowcharts, internal control questionnaires, compliance test, and the Government Accounting Standards Board Statement No. 07. Based on the analysis, be concluded that the system of internal control over fixed assets at Kantor Imigrasi Kelas 1 Pontianak is effective. However, there are several factors that must be taken to ensure that the system of internal control to be more effective is the inclusion of economic life and the percentage of depreciation, deletion of fixed assets that have been damaged and can not be used anymore, underwriting of fixed assets that have a high economic value and has an important role for the agency, as well as procurement transactions are recorded on the transaction date. Then the accounting policy for fixed assets are generally in accordance with Government Accounting Standards No. 7. Keywords: system of internal control, fixed asset